2020
DOI: 10.3390/cancers12123801
|View full text |Cite
|
Sign up to set email alerts
|

Tuft and Cancer Stem Cell Marker DCLK1: A New Target to Enhance Anti-Tumor Immunity in the Tumor Microenvironment

Abstract: Microtubule-associated doublecortin-like kinase 1 (DCLK1) is an accepted marker of tuft cells (TCs) and several kinds of cancer stem cells (CSCs), and emerging evidence suggests that DCLK1-positive TCs participate in the initiation and formation of inflammation-associated cancer. DCLK1-expressing CSCs regulate multiple biological processes in cancer, promote resistance to therapy, and are associated with metastasis. In solid tumor cancers, tumor epithelia, immune cells, cancer-associated fibroblasts, endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 105 publications
(129 reference statements)
0
35
0
Order By: Relevance
“…Hodgkin's lymphoma (HL) is the most common malignant lymphoma originating in the lymphoid hematopoietic system, especially in young adults [111]. Fan et al [112] showed that NEAT1 expression was significantly enhanced in HL tissues and cell lines, and NEAT1 downregulation resulted in inhibition of HL cell proliferation and invasion through the downregulation of doublecortin-like kinase 1 (DCLK1), an accelerator in tumor cell invasion, metastasis, and EMT [113], via interaction with miR-448.…”
Section: Hodgkin's Lymphomamentioning
confidence: 99%
“…Hodgkin's lymphoma (HL) is the most common malignant lymphoma originating in the lymphoid hematopoietic system, especially in young adults [111]. Fan et al [112] showed that NEAT1 expression was significantly enhanced in HL tissues and cell lines, and NEAT1 downregulation resulted in inhibition of HL cell proliferation and invasion through the downregulation of doublecortin-like kinase 1 (DCLK1), an accelerator in tumor cell invasion, metastasis, and EMT [113], via interaction with miR-448.…”
Section: Hodgkin's Lymphomamentioning
confidence: 99%
“…It was suggested that DCLK1 regulates migration, invasion and cell motility via activation of EMT (43), an important process for cancer initiation, cancer metastasis, and secondary tumor formation. However, expression of DCLK1 was also associated with impaired DNA repair (57,58), upregulation of WNT/b-catenin (59,60), RAS (13,61), PI3K/AKT (62) and VEGF (63,64) signaling, suggesting a multifaceted role of DCLK1 in cancer initiation and progression. Concordantly, our analysis of TCGA-HNSC dataset indicates that in HNSCC, tumors expressing higher DCLK1 mRNA levels were enriched for pathways that have been implicated in the EMT and CSC maintenance (such as NOTCH, WNT, TGFb, and hedgehog signaling), as well as for RAS and angiogenesis cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Salient developments in profiling CSCs based on their physiological and functional properties in PC has expanded the directory of inherent CSC markers such as overexpression of core stem cell transcription factors Oct4, Sox2, and Nanog [124], expression of doublecortin and Ca2 + /calmodulindependent kinase-like 1 (DCLK1) [125], and that of cell surface receptor leucine-rich repeat-containing G proteincoupled receptor 5 (Lgr5) [126]. DCLK1 has recently gained widespread recognition as a CSC marker in the pancreatic, colon, and other cancers [127], besides being an accepted tuft cell marker in the small intestine [127,128]. Studies have identified morphologically and functionally distinct subpopulations of tumorinitiating PC cells, in preinvasive (PanIN) and invasive pancreatic neoplasms, marked by the expression of DCLK1 and CSC-like properties [116].…”
Section: Other Potential Pancreatic Stem Cell Markersmentioning
confidence: 99%
“…DCLK1 has recently gained widespread recognition as a CSC marker in the pancreatic, colon, and other cancers [ 127 ], besides being an accepted tuft cell marker in the small intestine [ 127 , 128 ]. Studies have identified morphologically and functionally distinct subpopulations of tumor-initiating PC cells, in preinvasive (PanIN) and invasive pancreatic neoplasms, marked by the expression of DCLK1 and CSC-like properties [ 116 ].…”
Section: Other Potential Pancreatic Stem Cell Markersmentioning
confidence: 99%